Spontaneous uterine rupture in a patient who had previously undergone laparoscopic myomectomy (Case Report) (Faculty of Medicine Universitas Indonesia, 2005)
Following laparoscopic myomectomy, uterine rupture during pregnancy or delivery in the area of the scar is a very rare but dangerous complication. Individual cases of uterine rupture during pregnancy are described in the literature. Case report of uterine rupture during delivery in a patient who had previously undergone laparoscopic myomectomy. In the case presented here, the patient conceived 6 months after an 3.5 cm intramural myoma, had been laparoscopically removed. No symptoms suggesting uterine rupture were observed during the pregnancy, but in the first stage of delivery the condition of the patient deteriorated and symptoms of oligaemic shock developed. A laparotomy was performed, which showed the presence of 2100 gr fresh dead fetus in the abdominal cavity and ruptured uterine muscle in the scarred area about 5 cm. In patients who have previously undergone a laparoscopic myomectomy, there is some risk of uterine rupture at delivery. This is also the case where unappropriate suturing of the uterine muscleÂ had been required. (Med J Indones 2005; 14: 113-6) Keywords : delivery, infertility, laparoscopic myomectomy, uterine rupture.